Support of international organizations for a flexible development of corporate social responsibility in European countries - Dubcová, Gabriela (Univerzita Pardubice, 2007)
Current appreciation of corporate social responsibility. Fundamental theoretical principles of social responsible enterprise. Basic problem of support for social responsible enterprise - moral scepticism in business area. Result of questionnaire. Ethical problems in firm in Slovakia according to the selected order of respondents. Europe Commissions’ activities for a support of CSR expansion. Accelerating CSR practices in the new EU member states and candidate countries. Baseline scorecard for the region. Recommendations for project development.
Keywords: corporate social responsibility; social responsible enterprise; code of conduct; business ethics